Analisis Pengaruh Pola Makan terhadap Gastritis Menggunakan Metode PRISMA - Syahfitri, Rizky Indah; Zahroh, Diajeng Ayu Sekar; Sinaga, Haryanti; Tanjung, Hazira Yulistia; Fidorova, Yolanda; Tumanggor, Suro Rahmadhona (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Gastritis occurs due to inflammation in the lining of the stomach that can cause pain. Gastritis is often referred to by the term